2005
DOI: 10.1002/asi.20176
|View full text |Cite
|
Sign up to set email alerts
|

Distributed multi‐agent information filtering—A comparative study

Abstract: Information filtering is a technique to identify, in large collections, information that is relevant according to some criteria (e.g., a user's personal interests, or a research project objective). As such, it is a key technology for providing efficient user services in any large-scale information infrastructure, e.g., digital libraries. To provide large-scale information filtering services, both computational and knowledge management issues need to be addressed. A centralized (single-agent) approach to inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In recent years, Mukhopadhyay et al examined application of distributed agents to information filtering and classification tasks [19,20]. Their research using an Acquaintance List learning algorithm and other collaboration strategies showed that learning helped distributed agents do classification better without consuming too much communication resources.…”
Section: Related Workmentioning
confidence: 99%
“…In recent years, Mukhopadhyay et al examined application of distributed agents to information filtering and classification tasks [19,20]. Their research using an Acquaintance List learning algorithm and other collaboration strategies showed that learning helped distributed agents do classification better without consuming too much communication resources.…”
Section: Related Workmentioning
confidence: 99%
“…It identifies the desirable features of an IIR agent, including intelligent search, navigation guide, auto-notification, personal information management, personal preferred interface, and tools for easy page-reading. In [3] discusses two distributed information filtering approaches that are distributed with respect to knowledge or functionality, to overcome the limitations of single-agent centralized information filtering. Large-scale experimental studies involving the well-known TREC data set are also presented to illustrate the advantages of distributed filtering as well as to compare the different distributed approaches.…”
Section: Multi-agentmentioning
confidence: 99%
“…This agent module embedded in information retrieval system can analyze a certain user's behaviors, e.g., navigation (or browsing) and interactions for supporting them (Cothey, 2002;Hargittai, 2002). Such agent system can carry out manipulating the searching results by not only sorting (or ranking) them in order of relevance (Deters, 2001;Ruthven et al, 2003), but also filtering out noisy information from the list of them (Jung and Jo, 2003;Mukhopadhyay et al, 2005). Moreover, in multi-agent systems (MAS), a mediator agent plays an important role of coordinating the personal agents, in order to allow them to exchange meaningful information (or knowledge) between each other.…”
Section: Introductionmentioning
confidence: 99%